Space, society, and geography - National Seminar on "Indian Social Geography in the 21st Century, Challenges and Prospects" (2000 : Department of Geography, University of Mumbai); Banerjee, Swapna; Swapna Banerjee- Guha; University of Mumbai. Dept. of Geography (Jaipur : Rawat Publications, 2004)
Papers presented at the Seminar; with reference to India.
Fakulti Agro-Industri dan Sumber Asli.
Includes bibliographical references and indexes.
Keywords: Human geography -- India -- Congresses; Social interaction -- India -- Congresses